Transdermal Patches: Design and Evaluation - Bhandare Tejaswini S,; Dr. Khaire Rahul D,; Kathale Ankita A,; Korade Payal B,; Sankhe Lochani D,; Ghuge Samiksha K, (Asian Journal of Pharmaceutical Research and Development, 2025)
Transdermal drug delivery systems (TDDS) represent one of the most innovative and patient-friendly approaches to modern pharmacotherapy. Transdermal patches are medicated adhesive systems designed to deliver a specific dose of drug through the skin and directly into the systemic circulation, bypassing the gastrointestinal tract and hepatic first-pass metabolism. This review explores the design, mechanism, and evaluation of transdermal patches, highlighting the key components such as polymer matrices, permeation enhancers, and adhesives that influence drug release and absorption. Factors affecting drug permeation—including skin physiology, physicochemical properties of drugs, and formulation variables—are discussed in detail. Various types of patches such as single-layer, multi-layer, and microneedle-based systems are compared along with their applications in pain management, hormone therapy, and neurological disorders. The article further emphasizes recent advancements, including smart patches, dissolving microneedles, and 3D-printed delivery systems, which enhance therapeutic efficiency and patient compliance. Despite challenges like limited drug permeability and potential skin irritation, continuous innovations in nanotechnology, biomaterials, and active delivery mechanisms are expanding the scope of TDDS in personalized medicine.